Breast-related and body-related quality of life following autologous breast reconstruction is superior to implant-based breast reconstruction - A long-term follow-up study. (October 2021) - Miseré, Renée ML.; van Kuijk, Sander MJ.; Claassens, Eva L.; Heuts, Esther M.; Piatkowski, Andrzej A.; van der Hulst, René RWJ.
Abstract: Introduction: The better survival rates after breast cancer allow for setting of long-term goals, such as Quality of Life (QoL) and aesthetic outcomes following breast reconstruction. Studies find a higher breast-related QoL and greater satisfaction with breasts following autologous breast reconstruction (ABR) compared to implant-based breast reconstruction (IBR). However, aesthetic results from donor sites can influence body image. This concern is little addressed in the literature. Therefore, the aim of this study was to compare the long-term breast -related and body -related QoL of women who underwent ABR to women who underwent IBR. Material and methods: A multicenter, cross-sectional survey was conducted between November and December 2020 among women who underwent postmastectomy breast reconstruction between January 2015 and December 2018. A general questionnaire, the BREAST-Q, and the BODY-Q were used to collect data. Multivariable linear regression was performed to adjust differences in Q-scores for potential confounders. Results: In total, 336 patients were included (112 IBR, 224 ABR). Autologous reconstruction resulted in significantly higher mean scores in all subdomains of the BREAST-Q. On the BODY-Q, IBR scored significantly higher on scars, while ABR scored moderately to significantly higher on all other scales. Despite a lower mean score on Hips & outer thighs in women with Lateral Thigh Perforator (LTP) flap reconstruction, no negative influence on body image was found in these women. Conclusions: Long-term breast-related and body-related outcomes of ABR are superior to IBR. Donor site aesthetic does not adversely affect body image in women who underwent free flap breast reconstruction. Highlights: ABR patients reported better long-term breast-related QoL compared to IBR patients. DIEP flap reconstruction patients report high satisfaction with abdomen appearance. Donor site appearance does not affect body image in free flap reconstruction.